تدريس المفاهيم المجردة للطور التحضيري: دراسة ميدانية في عينة من ابتدائيات ولاية الوادي - الزهرة خلايفة; منال لموشي; مهاد حمي; سندس نعرورة (جامعة الوادي - University of Eloued, 2025)
الملخص: تهدف هذه الدّراسة إلى كشف واقع تدريس المفاهيم المجردة والغامضة لدى تلاميذ قسم التّحضيري، وذلك من خلال وصف المقرّر وعقد دراسة ميدانية في آراء الأساتذة عبر أداة الاستبيان في عينة مكونة من 20 أستاذا من أساتذة. باعتماد المنهج الوصفي في تقديم أسس نظرية عامة للموضوع ووصف المنهاج، والمنهج التّحليلي في كشف واقع تدريس المفاهيم المجرّدة، وكذلك المنهج الإحصائي في قراءة نتائج الاستبيان، توصلت الدراسة أنّ مقرّر الطور يشتمل على مفاهيم مجردة يصعب على المتعلمين استيعابها، خاصّة مع غياب الوسائل التعليمية الحديثة المساعدة على شرحها بطرق أسهل، مع كثرة عدد التلاميذ في الصف واختلاف مستوياتهم. ومنه نوصي بإعادة النظر في المقرر، وتوفير الوسائل التعليمية الضرورية، خاصة التكنولوجيا الحديثة. Abstract This study aims to explore the reality of teaching abstract and ambiguous concepts to preparatory class pupils, through describing the curriculum and submitting a questionnaire to a sample of 20 preparatory-level teachers. Using the descriptive approach to present a general overview of the topic and explain the curriculum, the analytical approach to examine the reality of teaching abstract concepts, and the statistical approach to interpret the questionnaire results, we found that the curriculum at this level includes abstract concepts that are difficult for learners to understand, especially with the lack of modern educational tools that can help explain them more easily, in addition to overcrowded classrooms and various levels of pupils. Therefore, we recommend reconsidering the curriculum content and providing the necessary educational materials, especially modern technological tools.
لسانيات عامة
Keywords: التّعليمية؛ اللغة العربية؛ المفاهيم المجردة؛ المنهاج؛ الطور الإعدادي; didactics; Arabic language; abstract concepts; curriculum; preparatory level.